The Effectiveness of Aspergillus fumigatus and A. niger in Biodegrading Petroleum Derivatives in Contaminated Water - Abbas Mohammed, Najwan (Al-Nahrain Journal of Science, 2026)
Fungi have attracted increasing attention in biodegradation due to their ability to degrade a wide range of substances through a process known as mycodegradation. This study evaluated that Aspergillus niger has a significant effect in biodegrading contaminated water samples. TPH concentrations in water samples before and after treatment with A. nigar ranged from 1,850 to 1,023 μg/l. TPH removal efficiency reached 44.7% with A. niger and 55.05% with A. fumigatus (from1.059 to 0.476 μg/l). The remaining PAHs were analyzed by GC-MS. The 10 not substituted PAHs on the list of important contaminants (EPA 10 PAHs) were the most frequently analyzed PAHs, with concentrations varying from oil to oil. A. fumigatus showed a higher degree of degradation of PAHs compared to A. niger. Treatment unit containing Aspergillus indicates to be effective in removing heavy metals and improving most physical and chemical properties and nutrients in industrial waste waters analyzed.